2017
DOI: 10.1155/2017/2603685
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A3 as a Prognostic Biomarker for Breast Cancer: A Retrospective Study

Abstract: To validate the correlation between ANXA3 expression and prognosis in breast cancer, a retrospective study encompassing 309 breast cancer patients was performed. The expression of ANXA3 was determined by the immunohistochemical examination of tissue sections by the Max Vision™ method. The ANXA3 levels in the patient samples were validated for the prognosis based on age, menopause status, tumor size, tumor node, metastasis stage, the number of lymphatic metastases, oncology grade, and molecular subtyping. An el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Specifically, ANXA3 expression in basal subtype of breast cancer (MDA-MB-231, HCC-70, HCC-1954) was found to be significantly higher than other subtypes (Kim et al, 2018). Other studies further confirmed that a significantly higher expression of ANXA3 was detect in TNBC cells in comparison to luminal A and B subtypes (Zhou et al, 2017b;Zhou et al, 2018). Furthermore, employing 2D-DIGE and iTRAQ approaches, Pendharkar et al demonstrated that ANXA3 upregulation is a marker for differentiating invasive ductal carcinoma with luminal B HER2 positive (LB) and HER2 enriched (HE) subtypes as well as their early and late stages (Pendharkar et al, 2016).…”
Section: The Diagnostic and Prognostic Value Of Anxa3 In Cancer Treatment And Managementmentioning
confidence: 84%
“…Specifically, ANXA3 expression in basal subtype of breast cancer (MDA-MB-231, HCC-70, HCC-1954) was found to be significantly higher than other subtypes (Kim et al, 2018). Other studies further confirmed that a significantly higher expression of ANXA3 was detect in TNBC cells in comparison to luminal A and B subtypes (Zhou et al, 2017b;Zhou et al, 2018). Furthermore, employing 2D-DIGE and iTRAQ approaches, Pendharkar et al demonstrated that ANXA3 upregulation is a marker for differentiating invasive ductal carcinoma with luminal B HER2 positive (LB) and HER2 enriched (HE) subtypes as well as their early and late stages (Pendharkar et al, 2016).…”
Section: The Diagnostic and Prognostic Value Of Anxa3 In Cancer Treatment And Managementmentioning
confidence: 84%
“…Further study confirmed that transfection of dendritic cells with ANXA3 activated autologous CD4 + T cells and CD8 + T cells to kill CD133 + hepatocellular carcinoma cells (28). Other previous studies have suggested that increased ANXA3 expression may be associated with the drug resistance of ovarian cancer (16,29), poor prognosis of breast cancer (29,30) and increased lymphatic metastasis (31).…”
Section: Discussionmentioning
confidence: 95%
“…Upregulation of the ANXA3 gene and its correlation with gastric tumor size, stage, and LNMs were detected by Wang et al [ 67 ] Moreover, these authors suggested that the overexpression of ANXA3 has a huge effect on gastric cancer malignancy, and it can be used as a novel prognostic biomarker and a suitable target for treatment [ 67 ]. Zhou et al reported that high expression levels of ANXA3 were significantly correlated with breast tumor LNMs and tumor grade, suggesting ANXA3 as a biomarker for breast cancer prognosis [ 68 ]. In our study, a significant overexpression of the ANXA3 gene in well-differentiated tumors compared with poorly differentiated tumors was instead observed.…”
Section: Discussionmentioning
confidence: 99%